Silencing c-Myc Enhances the Antitumor Activity of Bufalin by Suppressing the HIF-1α/SDF-1/CXCR4 Pathway in Pancreatic Cancer Cells - Liu, Xia (Front Pharmacol, 2020)
BACKGROUND: Pancreatic cancer is one of the most aggressive malignancies. Bufalin, a traditional Chinese medicine, has been used to treat pancreatic cancer as an antitumor agent although the mechanism by which it exerts its effects is still unclear. c-Myc has been found to be overexpressed in more than half of human cancers including pancreatic cancer. However, the role of c-Myc in pancreatic cancer cells and its influence in bufalin-treated pancreatic cancer are yet to be clarified. The present study aimed to investigate the role of c-Myc in the antitumor activity of bufalin in pancreatic cancer. METHODS: c-Myc siRNA and overexpression plasmid were transfected into pancreatic cancer cells to construct the cell models. c-Myc expression was detected via quantitative real-time polymerase chain reaction and western blot. The effect of c-Myc on bufalin-induced inhibition of cell proliferation was detected via CCK-8 assay. Cell apoptosis and the cell cycle were analyzed via flow cytometry. Cell invasion and migration was detected via Transwell and wound healing assays, respectively. In addition, the effect of bufalin on the suppression of tumor growth in vivo was studied in nude mice model subcutaneously injected with PANC-1 and SW1990 cells. Hematoxylin-eosin and terminal deoxynucleotidyl transferase dUTP nick-end labeling assay were used to evaluate pathological changes in vivo. The expression of HIF-1α/SDF-1/CXCR4 were detected via western blot. RESULTS: CCK-8 assay showed that bufalin could inhibit the proliferation of pancreatic cancer cell, and c-Myc downregulation enhanced this effect. Similarly, c-Myc downregulation enhanced the effect of bufalin on cell cycle arrest, apoptosis, and the invasion and migration of pancreatic cancer cell in vitro. Further mechanism assay showed that c-Myc enhances the effect by regulating the HIF-1α/SDF-1/CXCR4 signaling pathway. The in vivo studies verified the results that c-Myc enhances the effect of bufalin through regulation of the HIF-1α/SDF-1/CXCR4 pathway. CONCLUSIONS: Downregulation of c-Myc enhanced the antitumor activity of bufalin in pancreatic cancer cells by suppressing the HIF-1α/SDF-1/CXCR4 pathway. These findings indicate that c-Myc inhibitors could enhance the clinical therapeutic effect of bufalin and may expand the clinical application of bufalin accordingly.